2018
DOI: 10.4236/ojog.2018.813147
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Imbalance in Polycystic Ovarian Syndrome (Pcos) in Teaching Hospitals in Ekiti State, Nigeria

Abstract: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders of women at reproductive age and the major cause of anovulatory infertility. The aim of this study is to determine hormonal imbalance in women with PCOS in teaching hospitals in Ekiti State, Nigeria. Samples of 110 females (50 freshly diagnosed PCOS subjects and 60 healthy subjects) between the ages of 25-45 years old were collected from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
2
1
Order By: Relevance
“…In line with the report by Lv et al [26], estradiol levels in our study did not significantly differ between groups. However, this result disagreed with earlier findings by Ezeiruaka and Onitsha and Oyebanji et al [14,25]. The age range of the subjects in this study may account for this observed inconsistency.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In line with the report by Lv et al [26], estradiol levels in our study did not significantly differ between groups. However, this result disagreed with earlier findings by Ezeiruaka and Onitsha and Oyebanji et al [14,25]. The age range of the subjects in this study may account for this observed inconsistency.…”
Section: Resultscontrasting
confidence: 99%
“…This observed hyperandrogenism was in accordance with earlier studies by Ezeiruaka and Onitsha [14] and Oladoso et al [23]. Conversely, serum progesterone levels consistent with previous studies [14,25] were significantly lower in the PCOS group, indicating potential ovulatory dysfunction.…”
Section: Resultssupporting
confidence: 93%
“…[ 45 ] Oyebanji et al . [ 46 ] showed that PCOS women have higher levels of total testosterone, oestrogen and the LH/FSH ratio compared to non-PCOS. These hormones are expected to play a role in uric acid regulation, but the mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of EV causes a decrease in follicle-stimulating hormone hormones and their transformation into large follicles in ovarian morphology, such as cysts with atresia. While estradiol is the main female sex hormone controlling female reproduction during estrus and menstruation, high estrogen levels in the body can cause PCOS ( Oyebanji et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%